Reasons for consultation in the psychiatric out-patient clinic of a university teaching hospital in Nigeria: is this optimal use of psychiatrists’ time and expertise? (2003)
AIMS AND METHOD To identify activities that can be modified in the psychiatry out-patient clinic in order to improve the quality of services rendered. Consulting doctors obtained information on the reason for consultation and time spent by each patient over a one-month period. RESULTS Half of all the patients (50.5%) came for are peat prescription, and19.3% came for are peat prescription and counselling. The mean times spent on these two activities were 5.13 (s.d.=2.5) and 7.81 (s.d.=7.51) minutes, respectively. The time spent on these activities by doctors was 47%of the total clinic time. CLINICAL IMPLICATIONS Clinic services should be reorganised so that doctors can use their skills in more efficient and creative ways.